'If it can be used, it ain't science': one research department's dedicated approach to innovation. (3rd November 2008) - Telleman, Pieter; Hubner, Jorg; Orum, Mikael
MIC – Department of Micro- and Nanotechnology is a centre of excellence at the Technical University of Denmark (DTU). MIC has a strong tradition of transferring its research results to industry for productising. In the past decade, MIC has maintained an average rate of starting new companies of one each year. All these start-up companies have products on the market. MIC has also been instrumental in forming the basis for next generation technology products through collaboration with Danish industry. Commercialisation of research results requires a structured and systematic process that addresses leadership, culture, organisation, strategy, opportunity analysis, idea generation and selection and commercialisation. This paper describes our accumulative experiences of commercialisation of research results in an academic organisation. We also provide a brief look at the role of innovation in the Danish society and the role that universities play therein.